2020
DOI: 10.1097/meg.0000000000001755
|View full text |Cite
|
Sign up to set email alerts
|

Propofol alone prevents worsening hepatic encephalopathy rather than midazolam alone or combined sedation after esophagogastroduodenoscopy in compensated or decompensated cirrhotic patients

Abstract: Background This study was conducted to determine which type and dose of sedative drugs should be given to cirrhotic patients with compensation or decompensation during esophagogastroduodenoscopy (EGD) to prevent hepatic encephalopathy (HE) after sedation. Methods We reviewed the medical records of cirrhotic patients consecutively admitted to the hospital and conducted a number connection test (NCT) before and 2 h after EGD with moderate sedation. Sedation was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Quantitative analysis of cerebral blood supply and cerebral metabolism will help to assess the ischemic and hypoxic state of brain tissue and evaluate the therapeutic effect of drugs. The oxygen uptake rate in the brain can quantitatively reflect the degree of brain metabolism and D (a-jv) can be calculated by CaO 2 as the percentage of oxygen inhaled by brain neurons [16] . When cerebral blood flow decreases, the normal metabolic process can only be maintained by increasing the intake of blood oxygen in brain tissue and nerve cells.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis of cerebral blood supply and cerebral metabolism will help to assess the ischemic and hypoxic state of brain tissue and evaluate the therapeutic effect of drugs. The oxygen uptake rate in the brain can quantitatively reflect the degree of brain metabolism and D (a-jv) can be calculated by CaO 2 as the percentage of oxygen inhaled by brain neurons [16] . When cerebral blood flow decreases, the normal metabolic process can only be maintained by increasing the intake of blood oxygen in brain tissue and nerve cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the use of pharyngeal anesthesia under sedation with propofol have reported that pharyngeal anesthesia does not reduce the amount of propofol, improve endoscopists' satisfaction, or improve pharyngeal discomfort or patient satisfaction. [11][12][13][14] However, at present, benzodiazepines are more commonly administered than propofol to obtain optimal sedation during UGE, 9 as they do not require management by an anesthesiologist.…”
Section: Introductionmentioning
confidence: 99%